2022
DOI: 10.1017/qpb.2022.15
|View full text |Cite
|
Sign up to set email alerts
|

Exchange on dynamic encounter networks allows plant mitochondria to collect complete sets of mitochondrial DNA products despite their incomplete genomes

Abstract: Mitochondria in plant cells usually contain less than a full copy of the mitochondrial DNA (mtDNA) genome. Here, we asked whether mitochondrial dynamics may allow individual mitochondria to ‘collect’ a full set of mtDNA-encoded gene products over time, by facilitating exchange between individuals akin to trade on a social network. We characterise the collective dynamics of mitochondria in Arabidopsis hypocotyl cells using a recent approach combining single-cell time-lapse microscopy, video analysis and network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…To address how mitochondrial structure affects protein spread on a static network, recent modeling work showed that mitochondrial network snapshots that contain loops allow faster diffusive search compared to networks without loops [9, 10]. For spread on dynamic mitochondrial networks, a two-dimensional lattice model showed stronger dependence of effective diffusivity on connectivity for slower dynamics [31], a two-dimensional spatial model with mitochondrial motion along filaments suggested the rate of mitochondrial fusion impacts mitochondrial health [21], an aspatial model indicated more frequent fusion suppresses protein concentration fluctuations between mitochondria [37], and a model of heavily-fragmented mitochondria suggested mitochondrial DNA gene products efficiently spread (using a contact measure of spread) for parameters describing living plant cells [46]. These studies of dynamic networks considered spread through the mitochondrial network in a specific limit or as a secondary focus, and we are unaware of other work that focuses on how mitochondrial dynamics affect protein spread through the mitochondrial networks.…”
Section: Introductionmentioning
confidence: 99%
“…To address how mitochondrial structure affects protein spread on a static network, recent modeling work showed that mitochondrial network snapshots that contain loops allow faster diffusive search compared to networks without loops [9, 10]. For spread on dynamic mitochondrial networks, a two-dimensional lattice model showed stronger dependence of effective diffusivity on connectivity for slower dynamics [31], a two-dimensional spatial model with mitochondrial motion along filaments suggested the rate of mitochondrial fusion impacts mitochondrial health [21], an aspatial model indicated more frequent fusion suppresses protein concentration fluctuations between mitochondria [37], and a model of heavily-fragmented mitochondria suggested mitochondrial DNA gene products efficiently spread (using a contact measure of spread) for parameters describing living plant cells [46]. These studies of dynamic networks considered spread through the mitochondrial network in a specific limit or as a secondary focus, and we are unaware of other work that focuses on how mitochondrial dynamics affect protein spread through the mitochondrial networks.…”
Section: Introductionmentioning
confidence: 99%
“…Models for mtDNA segregation have typically regarded the cellular mtDNA population as well-mixed [36], but the mitochondria containing the population have varied morphologies and dynamics in different cell types, with important consequent and emergent properties [39][40][41][42]. Mitochondria can form cell-wide networks in some cell types, undergoing fission and fusion [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…2008 ) and that the location and dynamics of organelles influence their function and capacity for exchange and interaction ( Chustecki et al. 2021 , Giannakis et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%